A rare form of cardiac myxoma: interatrial septum tumor. Issue 9 (17th September 2020) - Kunioka, Shingo; Fujita, Kishu; Iwasa, Shizuko; Murakami, Hironori; Kamiya, Hiroyuki; Yamazaki, Kenji; Tsukui, Hiroyuki
Abstract: A myxoma is one of the most common tumors in cardiac surgery, with most of them originating from the left or right atrial walls and causing embolic complications. An 84-year-old woman was referred to our institution after echocardiography showed an interatrial septum tumor that was presumed to be a thrombus; however, postoperative pathological examination revealed it to be a cardiac myxoma. This atypical myxoma was covered with a solid capsule containing connective tissue and substantial calcifications, which had made it difficult to establish a diagnosis of myxoma.